Slippery magnetic track inducing droplet and bubble manipulation. Issue 8 (4th January 2022) - Chen, Wei; Zhang, Xiaolin; Zhao, Siyang; Huang, Jinxia; Guo, Zhiguang
Abstract : The prepared slippery magnetic track can realize the conversion between the slippery liquid-infused surfaces and the rough liquid-infused surfaces under the action of a magnetic field. Abstract : It is difficult for traditional droplet manipulation to combine transportation and rapid capture of droplets on an inclined surface. In this work, a slippery magnetic track (SMT) is presented to manipulate droplets and bubbles in a magnetic field. By changing the direction of the magnetic field, the transitions from non-pinning to pinning states on the SMT can be achieved. Through the SMT surface, it is possible to capture and release droplets and bubbles in the vertical direction. The detailed theoretical and experimental studies of droplet and bubble manipulation are discussed. This work demonstrates the versatility of magnetic manipulation, including the transition of droplet trajectory and bubble removal, which will facilitate the research of intelligent interfaces in energy transmission, drug transport and micro engineering.